Analisis Kausalitas Presepsi Keadilan Dan Dukungan Sosial Terhadap Perilaku Kewarganegaraan Organisasi (OCB) Di Industri Kreatif Vendor Event Jitu Music Center Sukabumi - Maulida, Nelis; Sari, Endah Murtiana; Windasari, Silviana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The creative industry, particularly the event vendor sector, faces challenges such as schedule uncertainty and flexible work structures, making organizational success highly dependent on Organizational Citizenship Behavior (OCB). This study aims to analyze the influence of distributive justice perception and social support on OCB among employees of Jitu Music Centre Sukabumi. It addresses a gap in previous studies that predominantly focused on formal sectors such as banking, education, and government, by directly examining causal relationships within the informal work context. The research employed a quantitative approach with purposive sampling techniques. Findings indicate that distributive justice and social support significantly affect OCB. Fair task distribution and support from supervisors and colleagues were proven to encourage extra-role behaviors that enhance organizational effectiveness. This study contributes theoretically by expanding OCB research into the informal creative sector and practically by providing insights for human resource management in fostering a fair, supportive, and collaborative work culture to improve organizational performance. In addition, this study enriches the literature by highlighting OCB as an adaptive mechanism in dealing with work uncertainty. The implications of the findings can serve as a foundation for developing HR policies that are more responsive to the needs of the creative sector. Thus, this research is not only relevant for academics but also offers practical benefits for creative industry practitioners in enhancing organizational competitiveness.